Bringing the outside in: The feasibility of virtual reality with people with dementia in an inpatient psychiatric care setting. (January 2021) - Rose, Vienna; Stewart, Inga; Jenkins, Keith G; Tabbaa, Luma; Ang, Chee Siang; Matsangidou, Maria
Background and objectives: Emerging research supports virtual reality use with people with dementia in the community, but is limited to this area, warranting further investigation in different care settings. The feasibility of virtual reality within an inpatient psychiatric care setting was therefore explored. Research design and methods: Eight people with dementia and 16 caregivers were recruited in January and February 2018 from a UK hospital specialising in progressive neurological conditions. A mixed methods design measured affect and behaviour using the Observed Emotion Rating Scale, Overt Aggression Scale-Modified for Neurorehabilitation and St Andrew's Sexual Behaviour Assessment. Thematic analysis was conducted following semi-structured interviews. Caregivers who worked at the hospital supported people with dementia throughout the process and were interviewed for their views on Head Mounted Display-Virtual Reality (HMD-VR) use with people with dementia. Results: HMD-VR was tried and accepted by people with dementia. Participants viewed HMD-VR positively as a 'change in environment' and would use it again. People with dementia experienced more pleasure during and after HMD-VR compared to before exposure, as well as increased alertness after. Three core themes emerged: 'Virtual Reality Experiences', 'Impact of Virtual Reality' and 'Experiences within the Virtual Environment'. Caregivers discussed preconceptions about virtual reality use and how these changed. Discussion and implications: This is the first study to explore the feasibility of HMD-VR with people with mild to moderately severe dementia in hospital and found that overall HMD-VR is viable. Findings evidence the clinical feasibility of HMD-VR implementation in this environment and inform future research.